On relations between creativity and quality management culture - Ceko, Enriko (Creativity Studies, 2021)
The goal of this study is to make evident the strong connections between creativity and quality management, since creativity and quality management subjects currently are observed with an increasing interest all around the world. The methodology of the research is based on the data collection and information about creativity index and ISO 9001:2015 standards, which are applied in developed, medium income developing countries, as well as in low income developing countries. It has been used a regressive analysis followed by analysis of variance, which resulted on the main conclusion of this study that relations between creativity and ISO standards application is strong. The main recommendation is that application of ISO standards relates mostly to quality and its management, and when it comes to quality of products or services, it refers specifically to the perception of extent to which products and services fulfill customer’s expectation and this is related to culture and creativity.